CHRONIC ENDOMETRITIS AND PELVIC PAIN - L. I. Maltseva; G. R. Smolina; E. J. Yupatov (Акушерство, гинекология и репродукция)
In 140 women of reproductive age with chronic endometritis by ultrasound with impulse dopplermetry examined the nature of the blood flow in the spiral and uterine arteries. A typical condition for patients was dilatation arcuate veins, set at 80% of the women, accompanied by pain in the lower abdomen varying severity. Combined extension arcuate veins and veins parametrium was observed in 15% of patients. In addition to chronic pelvic pain have been observed dyspareunia and dysmenorrhea. Every third patient along with the dilatation veins found increasing resistance index in the uterine and spiral arteries. For correction of impaired blood flow in the complex treatment included venotonics Flebodia 600, having a pronounced angioprotective effect. In the course of 3-6 months of treatment produced normalization of venous and arterial blood flow of the uterus and much more effective the treatment compared with patients who received no drug.